BIOSTIMULANTS, PLANT GROWTH REGULATORS, AND MICROORGANISMS IN IRRIGATED AGRICULTURE OF THE MIDDLE SAN FRANCISCO VALLEY: A REVIEW BASED ON DISSERTATIONS FROM 2015 TO 2024 - Martins, Marcelo da Silva; Garcia, Susana Zapata; Reis, Laíres Sale; Vieira, Nicolly Quirino Barros; Costa, William Ralf Santos; Pereira, Wiltemberg de Brito; Oliveira, Jadson Miranda; da Silva, Roberval Oliveira (Seven Editora, 2026)
The Middle São Francisco Valley is one of the main hubs of irrigated agriculture in Brazil, where technologies involving biostimulants, plant growth regulators, and microorganisms have been extensively studied with the aim of providing physiological support to crops, mitigating abiotic stresses, and promoting increases in yield and quality. This review aimed to analyze the published literature between 2015 and 2024, on the use of biostimulants, plant growth regulators, and microorganisms in irrigated agriculture in the São Francisco Valley, focusing on master’s dissertations from the graduate programs in Irrigated Horticulture (PPGHI – UNEB), Plant Production (PPGPV – UNIVASF), and Agricultural Engineering (PPGEA – UNIVASF). The review was conducted using dissertations available in the universities’ databases. For the selection of the works, specific filters were applied in each graduate program, considering the publication period (2015–2024) and the keywords (i) biostimulants, (ii) plant growth regulators, and (iii) microorganisms. Next, the dissertations were read and classified by year and by program, along with the identification of the topics addressed and the synthesis of the main results, as well as the most studied crops. The PPGHI – UNEB had the highest number of studies involving microorganisms, while the PPGEA and PPGPV programs at UNIVASF produced more research related to biostimulants and plant growth regulators. During the analyzed period, the most studied/researched crops were mango, melon, and grape. All programs in partnership with EMBRAPA company carried out outstanding work on this topic, contributing significantly to the scientific and technological advancement of irrigated agriculture in the region.DOI: https://doi.org/10.56238/sevened2026.008-061